ANALYSIS AND GENERALIZATION OF THEORETICAL POSITIONS ENSURE THE CAPITAL RESTORATION OF ENTERPRISES OF CONSTRUCTION INDUSTRY - Radkevych, A. V. (Science and Transport Progress, 2003)
The article, with the help highly-efficient flow algorithm and usage of intra-system links, on the basis of direct and dual problems, develops a theoretical substantiation of grounded selection of sub-contractor and timely and efficient renewals of buildings and installations.